Modification of Rubber (Hevea brasiliensis Muell. Arg.) Spacing for Long-term Intercropping - Sahuri, Sahuri; Cahyo, Andi Nur; Ardika, Risal; Nugraha, Iman Satra; Alamsyah, Aprizal; Nurmansyah, Nurmansyah (Journal of Tropical Crop Science, 2019)
Low prices of rubber has been a serious problem to rubber growers in Indonesia. Rubber-based intercropping systems offers a practical solution to this issue and increasing overall productivity, for example by growing upland rice and maize between the rubber tree rows. This study was aimed to determine the suitable spacing in rubber planting to facilitate long-term rubber-based intercropping systems. A field experiment was established in a smallholder rubber plantation in the Tanah Laut Regency, South Kalimantan with area of 50 ha. Two planting patterns of rubber clone PB260 were tested: (1) single row planting pattern (SR) by 6 m x 3 m, and (2) double row planting pattern (DR) by 18 m x 2 m x 2.5 m. The experiment showed that the girth of the rubber trees with the SR system at the 1st tapping year was slightly larger than that in the DR system, even though statistically it was not signifi cant. The latex yield per tree of SR and DR systems were similar, however, latex yield per hectare of SR system was higher than the DR system due to a higher tree population in the SR system. The DR system was technically suitable for long term intercropping, because when the rubber tree reached 8 to 9-year-old, the light penetration was > 80% at distance of about 4 m from the rubber tree rows. Economically, DR system can increase the added values for rubber farmers because it allows long term intercropping. Rubber-based intercropping with DR system is suitable to be applied, especially by smallholders, with a marginal benefi t cost ratio of around 2.07. Keywords: Hevea, intercropping system, rubber planting pattern, spatial arrangement